Sequential Au(I)-catalyzed reaction of water with o-acetylenyl-substituted phenyldiazoacetates - Zhou, Lei; Liu, Yizhou; Zhang, Yan; Wang, Jianbo (Beilstein Journal of Organic Chemistry, 2011)
The gold(I)-catalyzed reaction of water with o-acetylenyl-substituted phenyldiazoacetates provides 1H-isochromene derivatives in good yields. The reaction follows a catalytic sequence of gold carbene formation/water O–H insertion/alcohol-alkyne cyclization. The gold(I) complex is the only catalyst in each of these steps.
Keywords: alkyne; carbene O–H insertion; cyclization; diazo compounds; gold catalysis; 1H-isochromene